The importance of medication reconciliation in brazilian hospitals (Research, Society and Development, 2022)
The reconciliation of medications is directly related to the safety of people at different levels of health care in which medications are used as the main technologies for the cure, diagnosis and control of diseases. An integrative literature review was carried out to learn about the importance of medication reconciliation to ensure the safety of hospitalized patients. The bibliographic survey covered studies only in Portuguese, published between 2016 and 2021, in scientific journals and that were adequate to the theme proposed for the work, the research was carried out in November 2021 in the databases PubMed, SCIELO, CAPES portal, LILACS, Google academic and VHL, using the following descriptors: “drug reconciliation”, “hospital”, “Brazil” and “patient safety”. After analysis, 13 articles that comprised the study sample were identified. The results show that in most of the articles analyzed, medication reconciliation in hospitalized patients is fundamental for their safety. In all of them, we were able to see the importance of monitoring prescriptions and working together with the multidisciplinary team. Therefore, it was extremely important to carry out this integrative review to prove that pharmaceutical care is a positive tool for the health of the population. However, there was a lack of studies on medication reconciliation in Brazilian hospitals.